Medico-Legal Implications Of Dental Prenatal Age Estimation With Reference To A Case Report - Nambiar, P.; Paul, G.; Swaminathan, D.; Nadesan, K. (University of Malaya, 2000)
The estimation of age of human foetal remains is of great medico-legal importance. When the remains are intact and fresh, various morphological features such as crown-heel length, weight, appearance of ossification centres particularly around the ankles and knees and other parameters could be used to make a reasonable estimation of the period of gestation. In cases of criminal abortion, infanticide and child murder the question of age of the foetus, viability, live birth and a separate existence become very important. In practice, often at the time of detection, the remains are decomposed or skeletonised. In such a situation the examination of developing teeth will provide a reliable answer pertaining to the foetal age, the possibility of a separate existence and even the period of survival after birth. The.age determination from dental examination is possible from approximately 10 weeks intrauterine up to old age. The presence of neonatal line (birth line) in both dentine and enamel indicates live birth and a separate existence. It is possible that the time period of survival can be estimated by measuring postnatal deposition of these hard tissues. An intact human foetus that has undergone mild to moderate putrefaction was studied. The study of the morphological features and the ossification centres suggested that its approximate age was around nine months intrauterine. It was not possible to decide whether it was a live birth and had a separate existence. The examination of the developing first deciduous molar of the mandible suggested the approximate age was around 30-32 weeks intrauterine. The importance of examination of developing teeth in foetal remains (including neonates), particularly associated with putrefaction or skeletonisation is emphasized.